Study of Historicity in Salman Rushdie’s Midnights Children - SINGH, JAGBIR (Innovative Research Thoughts, 2017)
He's a global writer Salman Rushdie. It belongs to many civilizations. His legacy is partly contested and replicated in his books i.e., the individual's existential problems. The characters of Rushdie cause anguish in the readers' mind. His works generate tension in readers and provoke contradictory feelings. His claims on secularism and religion are much more ambiguous. Children of Rushdie's Mid Night have an intellectual and multicultural wealth. This book 'Midnight's Children' has been translated into 12 languages and discusses events of the subcontinent's pre- and post-Independence period. It deals with politics, religion and fanatism. The book is an allegory of contemporary India and a history and political family history. The book deals with two of the children's fates. The book is a connection between the country and the life of the protagonist, Saleem Sinai, the protagonist, and significant historical and political events. It is an account of society's impoverished and oppressed sectors. Rushdie tries to reconstruct his history via this book. The narrative of his life therefore coincides with the period and end of the National Emergency Movement. The book shows a conflict between a search for valour, personality and uniqueness, and the political deception..